Evaluation of hot dry rock reservoir stimulation based on microseismic monitoring method: a case study of the Northern Jiangsu Basin - Xu, Wenhao; Xie, Xinglong; Yi, Shanxin; Jin, Xianpeng; Guan, Junpeng; Chen, Jun; Yang, Yongbiao (Frontiers in Earth Science, 2025)
The reservoir stimulation is an indispensable part in the development of hot dry rock, and the evaluation of reservoir stimulation is particularly crucial for guiding the subsequent implementation of Enhanced Geothermal Systems (EGS). This paper proposes an evaluation method for the reservoir stimulation of hot dry rock based on microseismic monitoring, and establishes a microseismic monitoring system around the hot dry rock development site for practical application. Microseismic events are located based on the amplitude superposition method. The focal mechanisms for selected microseismic events are inverted through moment tensor inversion, followed by in situ stress inversions. Taking the focal mechanisms as constraint, both discrete fracture network model and continuous fracture network model are developed to invert the reservoir permeability and evaluate the stimulated reservoir volume. The results indicate that 5,449 monitored microseismic events are predominantly spatially distributed within 200 m near the well, with a dominant expansion direction oriented NW-SE. The focal mechanism primarily consists of strike-slip faults and normal faults, and the maximum horizontal stress direction within the reservoir also aligns with NW-SE. Permeability inversion reveals relatively high values in the NW direction, while the calculated stimulated reservoir volume is approximately 7.73 million m3. These research results improve the evaluation accuracy of reservoir stimulation, and provide a foundational basis for the development of hot dry rock.